2010
DOI: 10.1371/journal.pone.0013446
|View full text |Cite
|
Sign up to set email alerts
|

eXtraembryonic ENdoderm (XEN) Stem Cells Produce Factors that Activate Heart Formation

Abstract: BackgroundInitial specification of cardiomyocytes in the mouse results from interactions between the extraembryonic anterior visceral endoderm (AVE) and the nascent mesoderm. However the mechanism by which AVE activates cardiogenesis is not well understood, and the identity of specific cardiogenic factors in the endoderm remains elusive. Most mammalian studies of the cardiogenic potential of the endoderm have relied on the use of cell lines that are similar to the heart-inducing AVE. These include the embryona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 75 publications
5
62
0
Order By: Relevance
“…Hence, although we cannot compare the relative efficacies of hDE and END-2 cells, these both appear to be less potent than embryonic AL endoderm. The relatively modest inductive effect of hDE reported here may indicate that DE has less cardiomyogenic potency than VE, as recently reported using the mouse system [12,16]; we are currently preparing VE from pluripotent cells to examine this possibility in the human system. Although AL endoderm explanted from embryos appears to be more cardiomyogenic than that of cultured endoderm cells, it must be kept in mind that, with the exception of our recent study using mouse EBs [7], studies employing AL endoderm addressed its effect on gastrulation-stage target tissues [21,22], in contrast to this and other studies wherein inductive effects of cultured hDE and mouse endoderm cell-lines [13] were assessed on pluripotent cells.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Hence, although we cannot compare the relative efficacies of hDE and END-2 cells, these both appear to be less potent than embryonic AL endoderm. The relatively modest inductive effect of hDE reported here may indicate that DE has less cardiomyogenic potency than VE, as recently reported using the mouse system [12,16]; we are currently preparing VE from pluripotent cells to examine this possibility in the human system. Although AL endoderm explanted from embryos appears to be more cardiomyogenic than that of cultured endoderm cells, it must be kept in mind that, with the exception of our recent study using mouse EBs [7], studies employing AL endoderm addressed its effect on gastrulation-stage target tissues [21,22], in contrast to this and other studies wherein inductive effects of cultured hDE and mouse endoderm cell-lines [13] were assessed on pluripotent cells.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have shown that endoderm explanted from embryos [7], or endoderm-derived murine cell lines, can induce cardiomyogenesis in pluripotent ESCs [12][13][14][15][16]. The goal of this study was to extend this principle by establishing an all-human system, using endoderm cells that can be generated in large numbers under defined cell culture conditions.…”
Section: Induction Of Hdementioning
confidence: 99%
See 1 more Smart Citation
“…2B). Moreover, cXEN and embryo-derived XEN cells similarly express genes associated with parietal endoderm (Fst, Snai1, Pth1r, Pdgfra, Dab2, Emp2, Fxyd3, Atp6v0a1, Elf1, Foxq1, Col4a1, Lama1, Ttr and Stra6) (Kunath et al, 2005;Brown et al, 2010). Pearson correlation analysis confirms that cXEN and embryo-derived XEN cells have stronger correlation (R 2 value0.97±0.00) than the correlation between either mESCs and cXEN or embryo-derived XEN cells (R 2 value0.90±0.00) (supplementary material Fig.…”
Section: Research Article Development 139 (16)mentioning
confidence: 99%
“…qRT-PCR was performed using Quantace Sensimix on an Applied Biosystems 7500 machine (Life Technologies Corporation, CA, USA). Primer pairs were designed using Primer3 software or previously published (Molkentin et al, 1997; Fujikura et al, 2002;Niwa et al, 2005;Brown et al, 2010) and are listed in supplementary material Table S4. …”
mentioning
confidence: 99%